The Impact of Corporate Diversification and Financial Structure on Firm Performance: Evidence from South Asian Countries - Rashid Mehmood (Journal of Risk and Financial Management, 2019)
We examined the impact of corporate diversification and financial structure on the firms’ financial performance. We collected data from 520 manufacturing firms from Pakistan, India, Sri Lanka, and Bangladesh. We used panel data of 14 years from 2004–2017 to analyze the results. We applied a two-step dynamic panel approach to analyze the hypotheses. We found that product diversification and geographic diversification significantly affected the firms’ financial performance. We further found that dividend policy and capital structure had a significant impact on the firm’s financial performance.